Suicide rates in China, 2004-2014: comparing data from two sample-based mortality surveillance systems - Feng Sha; Qingsong Chang; Yik Wa Law; Qi Hong; Paul S. F. Yip (BMC, 2018)
Abstract Background The decreasing suicide rate in China has been regarded as a major contributor to the decline of global suicide rate in the past decade. However, previous estimations on China's suicide rates might not be accurate, since often they were based on the data from the Ministry of Health's Vital Registration ("MOH-VR") System, which is biased towards the better-off population. This study aims to compare suicide data extracted from the MOH-VR System with a more representative mortality surveillance system, namely the Center for Disease Control and Prevention's Disease Surveillance Points ("CDC-DSP") System, and update China's national and subnational suicide rates in the period of 2004-2014. Methods The CDC-DSP data are obtained from the National Cause-of-Death Surveillance Dataset (2004-2014) and the MOH-VR data are from the Chinese Health Statistics Yearbooks (2005-2012) and the China Health and Family Planning Statistics Yearbooks (2013-2015). First, a negative binomial regression model was used to test the associations between the source of data (CDC-DSP/MOH-VR) and suicide rates in 2004-2014. Joinpoint regression analyses and Kitagawa's decomposition method are then applied to analyze the trends of the crude suicide rates. Results Both systems indicated China's suicide rates decreased over the study period. However, before the two systems merged in 2013, the CDC-DSP System reported significantly higher national suicide rates (IRR = 1.18, 95% Confidence Interval [CI]: 1.13-1.24) and rural suicide rates (IRR = 1.29, 95% CI: 1.21-1.38) than the MOH-VR System. The CDC-DSP System also showed significant reversing points in 2011 (95% CI: 2006-2012) and 2006 (95% CI: 2006-2008) on the rural and urban suicide trends. Moreover, the suicide rates in the east and central urban regions were reversed in 2011 and 2008. Conclusions The biased MOH-VR System underestimated China's national and rural suicide rates. Although not widely appreciated in the field of suicide research, the CDC-DSP System provides more accurate estimations on China's suicide rates and is recommended for future studies to monitor the reversing trends of suicide rates in China's more developed areas.